Flow and heat transfer analysis on spiral counter flow heat recirculating burner - Othman, Muhammad Firdaus (2006)
In order to establish a performance characterization of spiral counter flow heat recirculating burner, an understanding of the chemical kinetics, heat transfer and flow dynamics aspects of the combustor needs to be developed. Research would be focusing on the micro-scaled square spiral counter flow configuration which is also known as the â€œSwiss rollâ€? micro-combustor with propane-air mixture as the case study. A two-dimensional Computational Fluid Dynamics (CFD) with propane-air premixed stoichiometric numerical based model is being adopted and focus of the study would be in observing the thermal characteristic (i.e. heat recirculation rate) of the combustor. This is the parameter that characterizes the preheat energy obtained by the incoming reactants through combustion process and its high energy postcombustion products. The performance of the combustor with respect to the thermal characteristic is being analyzed at a range of 40<Re<1000 steady, laminar and incompressible fluid flow velocity profile. In addition, a parametric study on identifying the effect of different geometrical aspect ratio between channel wall thickness to channel width is also being envisaged. Analysis has shown that a heat recirculation method has managed to produce an excess enthalpy flame beyond the adiabatic flame temperature which leads towards extending the limitation of the combustion process feasibility in a miniaturization of a combustor system.